Care for Patients With Neuromuscular Disorders in the COVID-19 Pandemic Era - Tseng, Yung-Hao; Chen, Tai-Heng (Frontiers in Neurology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has prompted a rapid and unprecedented reorganization of medical institutions, affecting clinical care for patients with chronic neurological diseases. Although there is no evidence that patients with neuromuscular disorders (NMD) confer a higher infection risk of COVID-19, NMD and its associated therapies may affect the patient's ability to cope with infection or its systemic effects. Moreover, there is a concern that patients with chronic NMD may be at increased risk of manifesting severe symptoms of COVID-19. In particular, as respiratory compromises account for the major cause of mortality and morbidity in NMD patients, newly emerging data also show that the risk of exacerbation caused by COVID-19 accumulates in this particular patient group. For example, patients with motor neuron disease and dystrophinopathies often have ventilatory muscle weakness or cardiomyopathy, which may increase the risk of severe COVID-19 infection. Thus, the COVID-19 pandemic may severely affect NMD patients. Several neurological associations and neuromuscular networks have recently guided the impact of COVID-19 on patients with NMD, especially in managing cardiopulmonary involvements. It is recommended that patients with moderate- to high-risk NMD be sophisticatedly monitored to reduce the risk of rapid decline in cardiopulmonary function or potential deterioration of the underlying NMD. However, limited neuromuscular-specific recommendations for NMD patients who contract COVID-19 and outcome data are lacking. There is an urgent need to properly modify the respiratory care method for NMD patients, especially during the COVID-19 pandemic. Conclusively, COVID-19 is a rapidly evolving field, and the practical guidelines for the management of NMD patients are frequently revised. There must be a close collaboration in a multidisciplinary care team that should support their hospital to define a standardized care method for NMD patients during the COVID pandemic. This article reviews evidence-based practical guidelines regarding care delivery, modification, and education, highlighting the need for team-based and interspecialty collaboration.